2000
DOI: 10.1080/026839600344410
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of IT support for knowledge management in the professions: an empirical study of law firms in Norway

Abstract: Knowledge management is an increasingly important source of competitive advantage for organizations. Knowledge embedded in an organization's business processes and an employee's skills provide a rm with unique capabilities for delivering a product or service to customers. Law rms represent an industry which seems very well suited for knowledge management investigation. Law rms are knowledge intensive and the use of advanced technology may transform these organizations in the future. To examine knowledge manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Research concerning the factors affecting KM has identified a number of different variables, from 'social' issues such as employee attitudes, top management support and social interaction culture [33][34][35] to 'technical' issues such as IT diffusion [40,41]. There are many organizations that relate KM to the implementation of new IT-based systems, neglecting organizational aspects such as human and social issues [42].…”
Section: Hsiu-fen Linmentioning
confidence: 99%
“…Research concerning the factors affecting KM has identified a number of different variables, from 'social' issues such as employee attitudes, top management support and social interaction culture [33][34][35] to 'technical' issues such as IT diffusion [40,41]. There are many organizations that relate KM to the implementation of new IT-based systems, neglecting organizational aspects such as human and social issues [42].…”
Section: Hsiu-fen Linmentioning
confidence: 99%
“…An enabling context: promoting a knowledge sharing culture The culture or climate of the firm has been found to be an important factor in the success, or perhaps more accurately, failure of a KMS (DeLong and Fahey, 2000;Gottschalk, 2000;Bock et al, 2005). Indeed, Butler and Murphy (2007) argue that the mixed findings about the success of KMS can be explained, at least in part, by considering the cultural context, in particular the organizational context.…”
Section: What Do We Mean By Knowledge?mentioning
confidence: 93%
“…With the latest technologies developed, it brings innovations on how employees perform their job. Technologies allows the expansion and universalising the scope of knowledge, and Tseng (2017); Kim and Park (2020) Gottschalk (2000) enhance the speed of knowledge transfer (Tseng, 2017). Applying various IT in KM implementation leads to numerous solutions such as groupware, workflow, content management, enterprise portal, e-learning, semantic Web and social media (Harandi, Nia & Valmohammadi, 2019).…”
Section: Technology Acceptancementioning
confidence: 99%